Vocabulary Breadth and Depth in Adults With Developmental Language Disorder. - Wang, Tingting; Hilker, Charlotte; Duff, Dawna; Hendrickson, Kristi (Journal of Speech, Language & Hearing Research, 2026)
Purpose: Developmental language disorder (DLD) affects approximately 7%-11% of children and often persists into adulthood, contributing to long-term challenges in education, employment, and health. Although vocabulary challenges are welldocumented in children with DLD, relatively little is known about how these difficulties manifest in adulthood. The current study examines vocabulary knowledge in adults with DLD along two dimensions: breadth (the number of words for which an individual can retrieve a meaning) and depth (quality of semantic knowledge for known words). Method: Vocabulary breadth was assessed using the standardized Peabody Picture Vocabulary Test-Fifth Edition (PPVT-5), while a novel scoring system was developed to evaluate vocabulary depth in a well-documented definition task (Wechsler Abbreviated Scale of Intelligence-Second Edition [WASI-II] Vocabulary subtest). Linear regression analyses were conducted to examine group differences between adults with DLD and peers with typical language (TL). Results: Adults with DLD (n = 39) scored significantly lower than did their peers with TL (n = 57) on both vocabulary breadth and depth. The vocabulary breadth measure (PPVT-5) yielded a numerically larger effect size than did the vocabulary depth measure (WASI-II). Conclusion: These findings characterize the long-term development of vocabulary skills in adults with DLD and highlight the importance of considering both vocabulary breadth and depth when assessing language profiles in adulthood.